Native barabaras, or sod huts, Karluk, Kodiak Island, Alaska, June 1906 - Cobb, John N. (John Nathan), 1868-1930 (1906)
Note from John Cobb field notebook: Karluk Village, Alaska. Includes Dr. Billings, Eng. Patterson and Bill. June 1906